Alternative Method of Surgical Treatment of Post-Infarction Left Ventricular Free Wall Rupture. Case Report - Ivashchenko, Volodymyr S.; Chyzh, Kostiantyn P.; Sokur, Serhii A. (Ukrainian Journal of Cardiovascular Surgery, 2023)
Acute myocardial infarction (AMI) is one of the causes of death in developed countries, despite the latest medical technologies. AMI is usually accompanied by numerous fatal complications. One of these complications is left ventricular free wall rupture (LVFWR). Myocardial rupture after AMI can occur from 1 day to 3 weeks after the infarction. Most ruptures occur 3-5 days after a heart attack. Left ventricular free wall rupture requires only emergency surgical intervention, which in most cases consists in applying U-shaped sutures or wrapping sutures using Teflon patch. The aim. To demonstrate an example of alternative surgical tactics and intraoperative management of a patient with myocardial infarction complicated by rupture of the free wall of the heart with the transition to cardiogenic shock. Case report. We presented the clinical case of patient V., 72 years old, who was delivered by ambulance on January 10, 2023 to the intensive care department of the National Amosov Institute of Cardiovascular Surgery (Kyiv, Ukraine). Main diagnosis: ischemic heart disease, acute coronary syndrome with ST-elevation myocardial infarction, cardiogenic shock. Conclusion. The only effective method of treatment of rupture of the free wall of the heart is surgical intervention. Using a sandwich patch with resection of necrotic areas of the myocardium and U-shaped sutures with Teflon patch passed from the side of the left ventricular cavity through the myocardium in the peri-infarct zone and through a patch from a vascular prosthesis allows hermetically sew up the LVFWR.